Evolution of late-stage metastatic melanoma is dominated by aneuploidy and whole genome doubling - Ismael A. Vergara (Nature Portfolio, 2021)
The genetic changes that occur in late stage metastatic melanoma are not well delineated. Here, the authors use rapid autopsy samples from metastatic melanoma patients and show that the late stage in the disease is characterised by whole genome doubling and aneuploidy.